2021
DOI: 10.3390/ijms22094922
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the Significance of Vitamin D Substitution in Monoclonal Gammopathies

Abstract: Vitamin D is a steroid hormone that is essential for bone mineral metabolism and it has several other effects in the body, including anti-cancer actions. Vitamin D causes a reduction in cell growth by interrupting the cell cycle. Moreover, the active form of vitamin D, i.e., 1,25-dihydroxyvitamin D, exerts various effects via its interaction with the vitamin D receptor on the innate and adaptive immune system, which could be relevant in the onset of tumors. Multiple myeloma is a treatable but incurable maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 158 publications
0
6
0
Order By: Relevance
“…The clinical significance of vitamin D and its metabolites in patients with MM is attributed to their participation in the regulation of calcium homeostasis and bone metabolism [ 24 ]. Vitamin D deficiency and insufficiency have been observed to cause a direct and erosive degradation of bone tissues, which is characterized by the manifestation of typical osteoclast markers, such as the formation of osteoclasts [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical significance of vitamin D and its metabolites in patients with MM is attributed to their participation in the regulation of calcium homeostasis and bone metabolism [ 24 ]. Vitamin D deficiency and insufficiency have been observed to cause a direct and erosive degradation of bone tissues, which is characterized by the manifestation of typical osteoclast markers, such as the formation of osteoclasts [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MGUS experience a 1.4–1.7 times greater occurrence of skeletal fractures [ 22 ], with a particular emphasis on vertebral fractures [ 23 ]. The deficiency of vitamin D facilitates the advancement of MGUS and SMM to MM by stimulating osteoclasts and enhancing osteoclastogenesis via the generation of various cytokines and molecules that possess the capability of osteoclast-activating factors (OAF) [ 24 ], including but not limited to interleukin-6 (IL-6), IL-1β, and IL-3 when interacting with the bone microenvironment [ 25 ]. The insufficiency of vitamin D may considerably augment the likelihood of advancement from a premalignant antecedent to MM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to HDL’s suppression during vitamin D deficiency, previous studies have linked low HDL levels to this condition [ 172 , 173 ]. A vitamin D deficit is frequently associated with an advanced stage of MM, an increased risk of progression, the development of pathological fractures, and a poorer prognosis [ 174 ]. Additionally, there is growing evidence, derived from both in vitro research and clinical trials, that vitamin D supplementation may be advantageous for patients with multiple myeloma as an adjuvant treatment.…”
Section: Hdl and Multiple Myelomamentioning
confidence: 99%
“…The use of medical plants has been demonstrated to be useful in hematological malignancies, and this fact is undoubtedly arousing because every day clinicians in hematology and oncology units are confronted with the adverse effects of traditional drugs, which can sometimes cause the stop of the treatment if it is intolerable for patients and dangerous for their health [ 57 , 58 , 59 , 60 , 61 ]. Scientific research showed the efficacy of different natural compounds both in the prevention and cure of cancer [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Cinnamon and Hematological Malignanciesmentioning
confidence: 99%